REPRESENTASI IDENTITAS BUDAYA JAWA DALAM PROGRAM ADILUHUNG JOGJATV - Rahmad, Cito Yasuki (Capture : Jurnal Seni Media Rekam, 2013)
The growth of private national TV stations has become the window for other culturesslowly erupting the local culture.This problem gives an opportunity to local TV stations tobecome an alternative TV station that represents the local culture in their presentation.Thisopportunity creates a room for mutualism symbioses between localTV stations and traditionalpeople with their particular cultures and traditions.â€œThe SuranTradition of Mbah Demangâ€ inModinan, Sleman will be the case to figure out the issue in this research which is entitled asâ€Javanese Culture Identity Representation inAdiluhung Program JogjaTVâ€.The case is the SuranTradition Ceremony of Mbah Demang.There are two major enquiries that this research will tryto find out the answer.Those are; how the type of this program is represented and why theJavanese culture identity is represented in this broadcast.Keywords: Representation,LocalTV,and Adiluhung